Breaking the Silence and Expanding the Discourse: Racioethnic Identity and Perceptions of Race Among People of the African Diaspora - Mary V. Alfred (Adult Education Research Conference, 2008)
Drawing from the postcolonial literature and using Afro-Caribbean people as a case example, this paper explores how colonialism and ethnicity influence perceptions of race and racism among people of the African Diaspora
Keywords: colonialism; postcolonial theory; racism; critical professionalism; adult education